The secret life of teens: Online versus offline photographic displays at home - Durrant, Abigail; Frohlich, David; Sellen, Abigail; Uzzell, David (Special Issue on "New Visual Technologies - Shifting Boundaries, Shared Moments", Visual Studies, 2011)
In this article we describe findings from a recent study in which we interviewed four British teenage girls about their photo display practices, online and offline, in family homes. We adopted a phenomenological approach to inquiry, with a particular interest in exploring how photographic representations of self and family signal self-development in emerging adulthood. Findings reveal how teens portrayed themselves differently to friends, online, and family, offline. Self-presentation to peers through photographs was managed separately from the family and largely free from parental control. The separate, online domain was used to explore alternative self-representations with real friends. Our findings appear to signal changing politics of photograph ownership and family representation between the generations.